Optimum Size of the Informal Credit Market - A Political Economy Perspective - Sugata Marjit; Suryaprakash Mishra (Center for Economic Studies and ifo Institute (CESifo), 2021)
Informality of markets is largely perceived as undesirable. Yet, ample evidence suggests that the informal sector contributes substantially in terms of income and employment in the entire developing world. In this paper, tax evaded income is invested in the informal credit market which in turn determines demand for labor in the informal sector and hence income of informal workers. Political authority cares about lost tax revenue due to evasion but is also concerned with politically adverse consequence of lower income of informal labor due to lack of investment in the informal sector. This trade off determines an optimum size of the informal credit market and the informal economy. The size is sensitive and non–monotonic with respect to changes in the tax rate and size of the labor force, depending on the tax revenue effect of tax policy, labor demand political sensitivity of the govt. towards lower wage in the informal sector.
Keywords: D78; H25; H26; H32; I18; O17; P48; 330; tax evasion; underreporting of income; informal credit market; political economy perspective